2019
DOI: 10.12659/msm.913889
|View full text |Cite
|
Sign up to set email alerts
|

Radix Tetrastigma Hemsleyani Flavone Suppresses Cutaneous Squamous Cell Carcinoma A431 Cells via Proteasome Inhibition

Abstract: BackgroundRadix Tetrastigma Hemsleyani Flavone (RTHF) has detoxification and anti-inflammation activity and is widely used. Here, we report that RTHF inhibits cell proliferation and induces apoptosis in cutaneous squamous cell carcinoma A431 cells and is a potential strategy for cancer therapy.Material/MethodsA431 cells were cultured in different concentrations of RTHF. The inhibition of cell proliferation was assessed by MTT assay, cell apoptosis was shown through FCM, and cell invasion was assessed by Transw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…According to the report, the main components of T. hemsleyanum extract are flavonoids, polysaccharides, and phenolic acids. Modern pharmacological studies have confirmed that the effective pharmacodynamic components of antitumor effect in T. hemsleyanum are mainly flavonoids, 19,20 flavonoids have a variety of pharmacological activities. 2123 Studies have shown that flavonoids constitute a significant proportion of the active ingredients in T. hemsleyanum , and they have been a focal point in the investigation of the plant's chemical constituents in recent years.…”
Section: Resultsmentioning
confidence: 99%
“…According to the report, the main components of T. hemsleyanum extract are flavonoids, polysaccharides, and phenolic acids. Modern pharmacological studies have confirmed that the effective pharmacodynamic components of antitumor effect in T. hemsleyanum are mainly flavonoids, 19,20 flavonoids have a variety of pharmacological activities. 2123 Studies have shown that flavonoids constitute a significant proportion of the active ingredients in T. hemsleyanum , and they have been a focal point in the investigation of the plant's chemical constituents in recent years.…”
Section: Resultsmentioning
confidence: 99%
“…In the in vitro experiments with different lung cancer cells (A549 cells and A431 cells), the total flavonoids of TDG can inhibit the proliferation and apoptosis of tumor cells, and its mechanism of action involves the Bcl-2 family proteins, Caspase family proteins, MAPK pathway, and the ubiquitin-proteasome pathway. Besides, the total flavonoids of TDG can markedly inhibit the metastasis and invasion of tumor cells, with migration and invasion being associated with the activation of MMPs and TIMPs proteins (Zhong et al, 2013;Zhong et al, 2016;Zhong et al, 2017;Zhong et al, 2019). The above studies indicate that the total flavonoids of TDG has a very good therapeutic effect on lung cancer at the cellular level.…”
Section: Pharmacological Activities Anti-tumor Activitymentioning
confidence: 92%
“…The pioneering work of Giard and collaborators ( 65 ), back in 1973, allow the establishment of 13 tumor cell lines, starting from more than 200 different tumor types, including carcinomas, sarcoma, melanoma, and brain neoplasms. From this work, the epidermoid carcinoma cell line A-431, derived from an 85-year-old female, started, and kept being used for experiments related to cSCC ( 66 68 ). Similarly, the epithelial cell line DJM-1, specifically derived from a malignant trichilemmal cyst cell, from an 87-years-old Japanese female ( 69 ), is considered as a good model for cSCC ( 70 73 ).…”
Section: In Vitro Modelsmentioning
confidence: 99%